EFFECT OF GLYCEROL ON PERFORMANCE AND SOME BLOOD CHARACTERISTICS OF HOLSTEIN CALVES - W. A. Khalid,; N. N. Al-Anbari, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was to study the effect of adding glycerol at different levels (T1 = control treatment without glycerol, T2 = 75 ml and T3 = 150 ml glycerol) in the body weight, body measurements and some blood characteristics of Holstein calves from 60 to 120 days of calves age. Body weight increased  (P≤0.05) in T3 calves at 80 and 100 days of age, also body weight increased in T2 and T3 calves at 120 days of age. T2 calves were significantly superior (P≤0.01) in average total gains from 60 to 120 days of age. Significantly increased (P≤0.05) at the ages of 100 and 120 days of: Wither height in T3 calves, Body length in T2 calves and Heart girth in T2 and T3 calves. Blood glucose concentration increased (P≤0.05) and blood NEFA concentration decreased (P≤0.01) in T2 calves at 80 days of age. At the age of 100 and 120 days, the concentration of blood glucose was increased (P≤0.01 and P≤0.05) and the concentration of NEFA and BHBA decreased (P≤0.01) in calves of the two treatments T2 and T3. We conclude that the addition of glycerol (75 and 150 ml/day) in the feeding of calves increases body weight, promotes growth and improves blood characteristics by increasing blood glucose and reducing NEFA and BHBA concentrations.